The role of communication in teaching of foreign language - Tynbayeva, G.S.; Mikhailova, N.B. (Вестник Карагандинского университета, 2016)
The article deals with the aspects of the using communicative methods in the English language teaching process. It is also shows an importance of interaction between teacher and students and students with students while studying foreign languages. There is an analysis of the effective methods and approaches of the use of interactive communication in the English language teaching, and the importance of attention during the pro- cess of studying the languages and developing listening, reading, writing and speaking skills. Communication increases student’s interest in the subject, enlarges the content of education, and modernizes educational process. Effective communication provides qualitative approach to education and plays an important role in studying.
Keywords: communication; interaction; conversation; attention; the English language; education process; pair or group activities; vocabulary; teaching; linguistic needs